1977
DOI: 10.1017/s0021853700015711
|View full text |Cite
|
Sign up to set email alerts
|

Royal Monopoly and Private Enterprise in the Atlantic Trade: The Case of Dahomey

Abstract: The kingdom of Dahomey is often presented as the classic instance of the operation of a royal monopoly of the Atlantic trade in West Africa. Detailed study establishes, however, that there was never any such royal commercial monopoly in Dahomey, although there were attempts to establish such a monopoly in the 1780s and in the 1850s. The kings of Dahomey enjoyed a number of commercial privileges, and controlled the distribution of the war captives taken by the Dahomian army, but they were never the sole sellers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Perhaps the most famous, and influential, of these examples was Karl Polanyi's argument that the kingdom of Dahomey enforced a monopoly over the cowry money supply in order to regulate the market in slaves after 1727. Subsequent research has suggested that the monarchical monopoly that Polanyi described was much more tenuous, and much less important, than he allowed (Polanyi 1964: 390;Law 1977;Johnson 1980). In Ghana itself there is undeniable evidence for the nineteenth-century Asantehene's control over gold specie, and for the revolutionary consequences of its disintegration (Arhin 1995: 99;McCaskie 1983;.…”
Section: Keith Breckenridgementioning
confidence: 99%
“…Perhaps the most famous, and influential, of these examples was Karl Polanyi's argument that the kingdom of Dahomey enforced a monopoly over the cowry money supply in order to regulate the market in slaves after 1727. Subsequent research has suggested that the monarchical monopoly that Polanyi described was much more tenuous, and much less important, than he allowed (Polanyi 1964: 390;Law 1977;Johnson 1980). In Ghana itself there is undeniable evidence for the nineteenth-century Asantehene's control over gold specie, and for the revolutionary consequences of its disintegration (Arhin 1995: 99;McCaskie 1983;.…”
Section: Keith Breckenridgementioning
confidence: 99%
“…Private enterprise was often restricted by the State, e.g. in Asante (Wilks 1979) and Dahomey (Law 1977;Manning 2004), and the systems of land allocation based on chiefs generated inefficient ownership structures and limited the possibility of economic development (Goldstein and Udry 2008). 11 In other words, it is possible that African societies had a relatively marked extractive character, in terms of their ability to concentrate resources and redistribute them unequally.…”
Section: A Long-term View On Inequalitymentioning
confidence: 99%
“…Reanalysis of most economic systems from Bronze Age Mesopotamia to 19th century West Africa has shown that the strong substantivist differentiation between contemporary and premodern economies is misplaced and gives unfounded importance to social-political integration or control over economies (Chaudhuri 1985;Latham 1978;Launay 1978;Law 1977Law , 1992Lynn 1992). This view, however, does not mean that traders and market mentalities have always dominated in past societies or will continue to dominate contemporary socioeconomic culture, or that laissez faire economies are the ''desired'' end of human economic development (Bogle 2005).…”
Section: An Argument For Trader Autonomy In Premodern Economiesmentioning
confidence: 99%